2019
DOI: 10.3390/ph12010032
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Chitosan Microparticles-in-Films for Buccal Delivery of Bioactive Peptides

Abstract: Nowadays, bioactive peptides are used for therapeutic applications and the selection of a carrier to deliver them is very important to increase the efficiency, absorption, release, bioavailability and consumer acceptance. The aim of this study was to develop and characterize chitosan-based films loaded with chitosan microparticles containing a bioactive peptide (sequence: KGYGGVSLPEW) with antihypertensive properties. Films were prepared by the solvent casting method, while the microparticles were prepared by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…Chitosan is a linear copolymer consisting of glucosamine and N ‐acetylglucosamine that exhibits a high degree of N ‐deacetylation. Chitosan‐decorated nanomaterials have currently been applied to the delivery of peptides, proteins, small molecules, genes, and multitheranostics drugs for satisfactory biodegradability, biocompatibility, and non‐immunogenicity in chitosan . Earlier studies also reported that chitosan and its derivative could inhibit the fibrillogenesis of amyloid β‐protein Aβ‐40 and/or age‐related diseases .…”
Section: Resultsmentioning
confidence: 99%
“…Chitosan is a linear copolymer consisting of glucosamine and N ‐acetylglucosamine that exhibits a high degree of N ‐deacetylation. Chitosan‐decorated nanomaterials have currently been applied to the delivery of peptides, proteins, small molecules, genes, and multitheranostics drugs for satisfactory biodegradability, biocompatibility, and non‐immunogenicity in chitosan . Earlier studies also reported that chitosan and its derivative could inhibit the fibrillogenesis of amyloid β‐protein Aβ‐40 and/or age‐related diseases .…”
Section: Resultsmentioning
confidence: 99%
“…However, low solubility under physiological pH possesses some limitations. Due to its mucoadhesive nature [101], CS has been used as a vehicle to deliver drugs to nasal [102], ocular [103], buccal [104], and pulmonary tissues [105]. For drug delivery purposes, CS is used in the form of nano/microparticles which is synthesized by emulsion, coacervation/precipitation, ionic gelation, reverse micellar methods, etc.…”
Section: Chitosan For Drug Deliverymentioning
confidence: 99%
“…The buccal delivery of APIs is an alternative, non-invasive route of administration that provides beneficial health effects. The buccal mucosa is a highly vascularized administration site, providing the high permeability for many APIs and the avoidance of the first pass effect [20]. Buccal formulations are recommended for pediatric dosage forms as they are patient-friendly and adjustable to the different physiological and pharmacokinetic profiles of infants, children and adolescents [21].…”
Section: Introductionmentioning
confidence: 99%